Pengaruh struktur kepemilikan, leverage dan sales growth terhadap manajemen laba dengan kualitas audit sebagai variabel moderasi pada perusahaan sektor teknologi di Bursa Efek Indonesia tahun 2019-2023 - Melindah Eka Zaputri; Ina Uswatun Nihaya (Universitas Negeri Surabaya, 2026)
This research aims to examine the influence of managerial ownership, institutional ownership, leverage, and sales growth on earnings management. This research is classified as quantitative research with a type of causality whose sample consists of 13 technology sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. Data analysis was carried out using panel data analysis with STATA version 17. The results showed that institutional ownership, leverage and sales growth had no effect on earnings management because companies with institutional share ownership and high sales growth and leverage tended to focus more on increasing company value. Managerial ownership affects earnings management, because high managerial ownership can reduce earnings management due to the dual role of managers in the company. Audit quality does not moderate the relationship between independent variables and earnings management. This is because the company has not focused on improving the quality of internal governance or the auditor does not have full access to monitor the entire process in financial reporting. This research contributes as a source of information for strategic company decision making regarding earnings management practices used for future company development.